THE RELATIONSHIP BETWEEN FAMILY SUPPORT IN ELDERLY HYPERTENSIVE ELDERLY WITH COMPLIANCE VISITS TO THE ELDERLY NEIGHBORHOOD HEALTH CENTER IN GUDO JOMBANG - Syaeful Islam; Ahmad Rifai; Anin Wijayanti (JIWA INTER PLUS, 2011)
Based on Household Health Surveyin 2007 showed that the prevalence of hypertension reaches0.37%, or 83 per 1,000members of the household. Approximately 0.15% of the number suffered by theelderly. In the elderly who suffer from hypertension requires an appropriate social support, because family support was instrumental in encouraging the elderly interestor willingness to participate in a neighborhood health center. To analyze the relationship between family support in elderly hypertensive elderly with compliance visits to the elderly neighborhood health centerin Gudo Jombang. This study used a cross section alanalyticdesign by taking a sample of 44 people is done by purposive sampling. Testing the data with SPSS version 17.0statistical test"Spearman Rank's" by rate=0.018<0.05. The study showed the majority of family support in elderly hypertensive elderly posyandu is a good category, indicating that most of the respondents came to posyandu elderly. Results of statistical test SpearmanRank's (=0.018<0.05). H1is accepted means that there is a relationship between family support for the elderly elderly hypertension with compliance visits to the elderly neighborhood health center. From the results of this study are expected to retain nurses and improve family and community empowerment by providing counseling or information about the importance of neighborhood health center visits to the elderly